2017
DOI: 10.1016/j.bpobgyn.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of uteroplacental and fetal Doppler in identifying fetal growth restriction at term

Abstract: Identification of the fetus at risk of adverse outcome at term is a challenge to both clinicians and researchers alike. Despite the fact that fetal growth restriction (FGR) is a known risk factor for stillbirth, at least two thirds of the stillbirth cases at term are not small for gestational age (SGA) -a commonly used proxy for FGR. However, the majority of SGA fetuses are constitutionally small babies and do not suffer from adverse perinatal outcome. Doppler cerebroplacental ratio (CPR) is emerging as a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 75 publications
0
56
2
6
Order By: Relevance
“…Previously, it has been suggested that CPR is a stronger predictor of adverse perinatal outcome in suspected late‐onset FGR than in suspected early‐onset FGR. Unexpectedly, our subgroup analysis showed the opposite; there was a higher predictive accuracy for adverse perinatal outcome in pregnancies with suspected early‐onset FGR.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Previously, it has been suggested that CPR is a stronger predictor of adverse perinatal outcome in suspected late‐onset FGR than in suspected early‐onset FGR. Unexpectedly, our subgroup analysis showed the opposite; there was a higher predictive accuracy for adverse perinatal outcome in pregnancies with suspected early‐onset FGR.…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, subgroup analyses suggest that the predictive accuracy of CPR is higher in pregnancies with suspected early-onset FGR and when MCA-PI/UA-PI ≤ 1.08 or MCA-RI/UA-RI < 1 or < 1.05 is used as the definition of abnormal CPR. Previously, it has been suggested that CPR is a stronger predictor of adverse perinatal outcome in suspected late-onset FGR than in suspected early-onset FGR 23,[25][26][27] . Unexpectedly, our subgroup analysis showed the opposite; there was a higher predictive accuracy for adverse perinatal outcome in pregnancies with suspected early-onset FGR.…”
Section: Main Findingsmentioning
confidence: 99%
“…Similar results were reported by Triunfo et al 58 who showed that a low CPR in the third trimester of pregnancy had a higher association with adverse perinatal outcomes such as, nonreassuring fetal status requiring emergent cesarean section, 5-minute Apgar score <7, or neonatal metabolic acidosis at birth (UA pH ≤7.15 and base excess greater than 12 mEq/L) than EFW. These observations led to the evaluation of the CPR as a screening tool for pregnant women during the third trimester of pregnancy to identify fetuses at risk of late SGA, 5962 stillbirth, low pH in the umbilical cord, low Apgar scores, cesarean delivery for fetal distress, and admission to the neonatal intensive care unit. 6062 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of uterine artery (UtA) Doppler indices assessed during the third trimester of pregnancy in identifying fetuses at risk of adverse outcome is increasingly reported in literature . Several authors have indeed demonstrated that small fetuses with abnormal (≥95th centile) mean UtA pulsatility index (PI) during the third trimester are at increased risk of adverse perinatal outcome and show placental signs of underperfusion .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical utility of uterine artery (UtA) Doppler indices assessed during the third trimester of pregnancy in identifying fetuses at risk of adverse outcome is increasingly reported in literature. 1 "Reproducibility Issue" in biological sciences. 4 Obstetric measurements, and Doppler in particular, are not immune from these concerns, and a debate is currently ongoing on which cutoffs should be used to interpret reproducibility studies.…”
Section: Introductionmentioning
confidence: 99%